A compound formulation of EGF-modified paclitaxel micelles and EGF-modified emodin micelles enhance the therapeutic effect of ovarian cancer. (2nd January 2023) - Tang, Ling; Liu, Xiu-Xiu; Yang, Xiao-Dan; Tan, Shuang; Zou, Zhong-Wen
Abstract: Ovarian cancer is a serious threat to female health, although the incidence of it is relatively low, its mortality rate remains high due to its intense invasion and metastasis. Therefore, it is urgent to explore new treatment strategies for ovarian cancer. In this study, paclitaxel and emodin were encapsulated in different micelles, and loaded on the surface of the micelles with epidermal growth factor (EGF) as the targeting molecule, made compound formulations in proportion. In this study, EGF-modified paclitaxel micelles and EGF-modified emodin micelles were characterized, their inhibitory effects on SKOV3 cell proliferation and invasion were studied in vivo and in vitro, and its targeting ability was confirmed. The results showed that the shape, particle size, zeta potential, release rate, encapsulation rate, polydispersity index, and other physical and chemical properties of EGF-modified paclitaxel micelles plus EGF-modified emodin micelles meet the requirements, and the modification of EGF on the micelle surface could obviously improve the uptake of SKOV3 cells and inhibit the proliferation of SKOV3 cells. The compound formulation can inhibit the invasion and metastasis of ovarian cancer by inhibiting the expression of hypoxia inducible factor-α, MMP-2, MMP-9, and VE-cadherin. The in vivo studies have also showed significant pharmacodynamics results. These results indicated that EGF-modified paclitaxel micelles plus EGF-modified emodin micelles provide a new strategy for the treatment of ovarian cancer.